The impact of material management on construction project delivery in Somalia - Wayrah, Mohamed Yusuf; Sarpin, Norliana; Mohamed, Sulzakimin; Masrom, Md. Asrul Nasid (UTHM Publisher, 2021)
Materials management practice is a procedure that coordinates planning, requirement assessment, sourcing, purchasing, transporting, materials storing and controlling, wastage minimisation and cost reduction for profit optimization. Material management have been a great problem to most firms in the construction industry due to a tendency of mismanagement of materials. The scale of activities concerning materials management increases as the size of the contract increase. This study centered on the impact of materials management practices in the Somalia construction project delivery. The objectives of this study are to investigate the current practice of material management at construction projects, to identify the causes of ineffective material management, and to examine the impact of material management process to the construction project delivery. A questionnaire survey was conducted to collect data from Grade A contractor company in Mogadishu, Somalia and the respondent consist of project managers, civil engineers, architect and site managers. The findings revealed that current practice of material management in construction projects in Somalia include identifying the needed materials, consideration of site layout and location, material available close to site, material conform with specifications and material supplied on-time. The study also found that most common root causes of ineffective material management were undefined scope, incomplete drawings, inadequate information on material supply, poor scheduling of material on site, no determination of what and when the material needed and lack in determining the quantity of material needed. Furthermore, the respondents of this research indicated that the occurrence of cost overrun and delay in progress of the work are the major impacts of ineffective material management that bring negative impact to the construction project delivery in Somalia. The research concludes that effective material management practice can improve the overall handling of material and smooth project delivery on site. A proper planning of material management practice right from the start of the project execution should be practiced on site in order to ensure timely execution of the project and standard of the work delivery within reasonable cost, time and quality.